Optimizing the Determination of Tutor Professionalism Fields Based on the PROMETHEE Method at LPK2 Pascom Medan - Eferoni Ndruru; Fince Tinus waruwu; Mardiah Nasution; Arfiana Agustiana Tarigan (STMIK Methodist Binjai, 2026)
The alignment between tutors' professional expertise and their competencies is a key factor in creating effective learning processes at LPK2 Pascom Medan, a computer education and training institution. The current practice of assigning tutors to teaching fields relies primarily on managerial judgment, resulting in decisions that may not be entirely objective due to the need to consider multiple criteria, including educational background, teaching experience, professional certifications, technical competence, and performance evaluation results. This complexity necessitates a systematic approach to support decision-making. This study aims to design and implement a Decision Support System for determining tutors' professional specialization by applying the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE). The PROMETHEE method was selected because it can evaluate and rank alternatives based on multiple criteria through the calculation of leaving flow, entering flow, and net flow values. The research methodology consists of problem identification, data collection through observation, interviews, and documentation, determination of evaluation criteria and their respective weights, followed by the calculation and ranking of alternatives using the PROMETHEE method. The expected outcome is a Decision Support System capable of providing objective, consistent, and transparent recommendations for assigning tutors to appropriate professional fields. The proposed system is expected to improve the accuracy of tutor placement, enhance the quality of learning, and serve as a valuable reference for human resource management in education and training institutions.